Determinan Kualitas Laba Perusahaan yang Terdaftar di Jakarta Islamic Index Tahun 2023-2024 - Khoirunnida, Sal Sabila; Zaky, Achmad (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study aims to examine the effects of the corporate tax to turn over ratio, related party transactions, non-halal income, and interest-based debt on earnings quality. Panel data were collected from 37 sample companies listed in the Jakarta Islamic Index 70 on the Indonesia Stock Exchange during the 2023–2024 period. Data analysis was conducted using multiple linear regression. The results indicate that the hypotheses stating that the corporate tax to turnover ratio, related-party transactions, and interest-based debt negatively affect earnings quality are not supported, whereas the hypothesis stating that non-halal income has a positive effect on earnings quality is supported. These findings suggest that tax management practices, related-party transactions, and the use of interest-based debt conducted within reasonable limits do not create pressure for management to engage in earnings manipulation. Furthermore, non-halal income that remains within sharia tolerance thresholds continues to be recognized as part of corporate income and is capable of generating real cash flows, thereby contributing to improved earnings quality.